2017
DOI: 10.1371/journal.pone.0175777
|View full text |Cite
|
Sign up to set email alerts
|

Tissue expression profiles and transcriptional regulation of elongase of very long chain fatty acid 6 in bovine mammary epithelial cells

Abstract: In mammals, very long chain fatty acids (VLCFAs) perform pleiotropic roles in a wide range of biological processes, such as cell membrane formation, cell signal transduction, and endocrine regulation. Beef and milk are abundant of palmitic acid which can be further elongated into stearic acid for synthesizing VLCFAs. Elongase of very long chain fatty acid 6 (ELOVL6) is a rate-limiting enzyme for converting palmitic acid to stearic acid. Consequently, investigating the tissue expression patterns and transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Moreover, the supply of ALA strengthen the binding of SP1 to the ELOVL7 proximal promoter, which leading to the accumulation of lipid droplets in bMECs. Our previous research discovered that SP1 bound at the promoter of bovine ELOVL6 to regulate its transcription (Chen, He, & Liu, ), which were proven to be the similar regulation pattern for the expression of ELOVL7 in the present study. These results illustrate that ELOVL7 appear to play an important role in lipogenesis, and extend our knowledge of bovine ELOVL7 in controlling lipid synthesis of mammary gland lipid in cattle, in addition, enlightening us the profound role of SP1 involving in the lipid metabolism.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, the supply of ALA strengthen the binding of SP1 to the ELOVL7 proximal promoter, which leading to the accumulation of lipid droplets in bMECs. Our previous research discovered that SP1 bound at the promoter of bovine ELOVL6 to regulate its transcription (Chen, He, & Liu, ), which were proven to be the similar regulation pattern for the expression of ELOVL7 in the present study. These results illustrate that ELOVL7 appear to play an important role in lipogenesis, and extend our knowledge of bovine ELOVL7 in controlling lipid synthesis of mammary gland lipid in cattle, in addition, enlightening us the profound role of SP1 involving in the lipid metabolism.…”
Section: Resultssupporting
confidence: 78%
“…Limited researches have indicated that ELOVL7 was activating by hormonal status, including insulin and androgen via sterol regulatory element binding transcription factor 1 (SREBF1) (Rodriguez‐Cruz, Sanchez Gonazalez, Sanchez Garcia, & Lopez‐Alarcon, ; Tamura et al, ). However, our previous research discovered that transcription factor Sp1 (SP1) bound at the promoter of ELOVL6 to regulate its transcription (Chen, He, & Liu, ), which enlightened us the similar regulation pattern for the expression of ELOVL7 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the role of ELOVL5 and ELOVL6 in the synthesis of FAs is of great importance for beef cattle breeding programs [24, 64, 65]. The investigation into the molecular mechanism of the ELOVL gene family can provide valuable insight into improving the composition of beneficial FA in cattle and expanding our knowledge of transcriptional regulation mechanisms in domestic animals [66].…”
Section: Discussionmentioning
confidence: 99%
“…ELOVL6 activity characterised by cloning of mammalian ELOVL6 ORF into expression vector and expressing the vector in mammalian cells shows that ELOVL6 specifically catalyses the elongation of ECSFA and MUFA with chain lengths of 12, 14 and 16 carbons (46,50) . ELOVL6 is found to be ubiquitously expressed in mice and bovine tissues (29,46) , and --------------------- --------------------- Human YLSYLVLFCHFFFEAYIGKMRK-TTKAE--265 Mouse YLSYLVLFCHFFFEAYIGKVKK-ATKAE--267 Rat YLSYLLLFCHFFFEAYIGKVKK-ATKAE--267 Monkey YLSYLVLFCHFFFEAYIGKMRK-TTKAE--265 Cattle YLSYFVLFCHFFFEAYIGSKMRKATKAD--264 Chicken YLSYFVLFCHFFFEAYIGKTTKARKVD---265 Frog YLSYFVLFCHFFFEAYITKTRKASKAD---265 Catfish YLSYFVLFCQFFFEAYINKTKSKNNAKKIQ 267 Zebrafish YLSYFVLFCQFFFEAYITKRKSNAAKKSQ-266 -------------I II III IV Fig. 1.…”
Section: Discussionmentioning
confidence: 99%